Mechanical signaling regulates vascular smooth muscle cell adaptation in aging - Mohajeri, Amin; Shin, Song Yi; Padgham, Samuel; Boland, Devon J.; Pittman Ratterree, Dana; Blizman, Jacob; Han, Gang; Woodman, Christopher R.; Trache, Andreea (Frontiers in Physiology, 2025)
Aging is an independent risk factor for cardiovascular disease. Preventing age-induced arterial dysfunction and the associated risk of cardiovascular disease remains a significant clinical challenge. Aerobic exercise, which induces a temporary increase in both blood flow and pressure in active tissue, has been shown to reduce macroscale arterial stiffening in humans. This study investigates the effects of mechanical stimuli on improving aging pathophysiology of vascular smooth muscle (VSM) cells isolated from soleus feed arteries (SFA). We hypothesized that age-induced impairment of VSM contractility can be rescued by mechanical stimulation that enhances formation of smooth muscle alpha-actin (SMα-actin) fibers and cell-matrix adhesions in aged VSM cells. Ex-vivo functional studies were used to assess myogenic contractility of VSM in isolated SFA from young (4 months) and old (24 months) Fischer 344 rats. These data indicated that pre-treatment of isolated aged SFA with a short-duration increase in intraluminal pressure rescued contractility. The mechanical stretch-induced remodeling of the cellular architecture was assessed in VSM cells isolated from young and old SFA. To dissect the mechanisms involved, the structural and functional properties of VSM cells were assessed by using mechanical stimulation combined with fluorescence confocal microscopy. Results showed that aged VSM cells respond faster than young cells to 2D biaxial cyclic stretch by increasing actin stress fiber formation and vinculin recruitment at cell-matrix adhesions. In addition, hydrostatic pressure treatment applied to aged VSM cells plated on stiffer substrates restored actin fibers and integrin β1 recruitment. Taken together, these findings suggest that discrete VSM cell mechanical properties and their ability to adapt to external mechanical signals are key in restoring VSM contractility in aging. These results are significant because they provide a novel understanding of the mechanisms by which mechanical stimulation improves VSM contractility in aged resistance arteries. Our results provide new insights into the role of VSM in vascular aging and highlight a new direction for mitigating age-related effects via mechanical stimulation-induced VSM remodeling.